Hubungan Kecemasan Sosial dan Kematangan Emosi dengan Kematangan Seksual Remaja SMP di Kabupaten Bantul Yogyakarta - Endang Sri Lestari (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2012)
This research aims to find out some factors related to the sexual maturity, such as the social anxiety and emotional maturity on the adolescents of the SMP in Kabupaten Bantul, Yogyakarta. The hypotheses which are presented in this research are: First; there is a relation between the social anxiety and emotional maturity towards the sexual maturity; Second, there is a negative relation between the social anxiety and sexual maturity; Third, there is a positive relation between the emotional maturity and sexual maturity.The research participants were 70 male and female adolescents in SMP N 2 Banguntapan, Kabupaten Bantul. The data gathering was carried out in two phases, First, by applying the sampling area technique in order to determine the research location and Second, by applying the cluster random sampling technique to determine the research sample subject. Meanwhile, the research instrument which was employed was the scale of social anxiety, emotional maturity and sexual adolescents maturity. The double-regression technique was applied to analyze the data in this research.The result of this research showed that: First, there was a relation between social anxiety and emotional maturity towards the sexual maturity in adolescentsof the SMP in Kabupaten Bantul, Yogyakarta (R=0,667, R2=0,445, F-regression= 26,911 and the significant level for about p< 0,01). Second, there was a negative relation between the social anxiety and sexual maturity in adolescentof the SMP in Kabupaten Bantul, Yogyakarta (R partial=0,632, p=0,01). Third, there was a positive relation between the emotional maturity and sexual maturity in adolescebtsof the SMP in Kabupaten Bantul, Yogyakarta (R partial=0,358, level p<0,01).Key words: Â Sexual Maturity, Social Anxiety, Emotional Maturity.